The challenge of telecommuting implementation in Malaysian government offices - Abd Razak, Rafidah; Mat Aji, Zahurin; Sheik Osman, Wan Rozaini; Othman, Nafishah; Wahid, Juliana (Idea Group Inc., 2006)
Telecommuting is no longer an option for organization today, as people have more choices in the type of jobs or organization they want to work with. With education, knowledge, sophisticated but affordable information and communication technology (ICT), people can now choose to work for one or more employers. Telecommuting becomes one of the choices for the employees in most organizations in developed countries. In Malaysia, telecommuting is still in its infancy. However it is hope that as ICT become more common in the country, telecommuting will be an alternative work option to Malaysians. Telecommuting can be a liberating option for physically challenged, retires, and workers who may otherwise have had to drop out from labour force due to social obligations at home or otherwise. In this study we investigate Malaysian senior government civil servants’ attitudes concerning telecommuting. The study identifies the factors that support telecommuting implementation in Malaysian government offices. Using the Delphi technique, a group of senior government civil servants were asked to identify potential impact of telecommuting in government offices.The items were recorded and analyzed. The group identified seven factors determined to be very important to support the implementation of telecommuting. The factors are rules, regulation and policies, infrastructure,finance, selection,training, environment and benefits. Explanations are offered for each factor and areas for further research are also discussed.